2020
DOI: 10.1111/btp.12774
|View full text |Cite
|
Sign up to set email alerts
|

Coping with branch excision when measuring leaf net photosynthetic rates in a lowland tropical forest

Abstract: Measuring leaf gas exchange from canopy leaves is fundamental for our understanding of photosynthesis and for a realistic representation of carbon uptake in vegetation models. Since canopy leaves are often difficult to reach, especially in tropical forests with emergent trees up to 60 m at remote places, canopy access techniques such as canopy cranes or towers have facilitated photosynthetic measurements. These structures are expensive and therefore not very common. As an alternative, branches are often cut to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Measurement on detached branches were conducted no longer than 45 minutes after collection. Previous studies investigating measurements of gas exchange on severed or attached branches found no significant differences between the two methods (Bader et al, 2016; Verryckt et al, 2020). A–C i curves were measured at a Q of 1800 μmol m -2 s -1 (in 2015 and 2019) or 1200 μmol m -2 s -1 (in 2017) and at a leaf temperature of 25 °C.…”
Section: Methodsmentioning
confidence: 76%
“…Measurement on detached branches were conducted no longer than 45 minutes after collection. Previous studies investigating measurements of gas exchange on severed or attached branches found no significant differences between the two methods (Bader et al, 2016; Verryckt et al, 2020). A–C i curves were measured at a Q of 1800 μmol m -2 s -1 (in 2015 and 2019) or 1200 μmol m -2 s -1 (in 2017) and at a leaf temperature of 25 °C.…”
Section: Methodsmentioning
confidence: 76%
“…Photosynthetic capacity by mass (Amass, nmol CO2 g -1 s -1 ): Photosynthetic capacity was measured on six leaves from two sun-lit branches in both tropical forest sites using a LI-6400 portable photosynthetic system (LI-COR, Lincoln, NE, USA). Branches for photosynthesis determination were placed in a bucket of water during the measurements to avoid disruption of water transport within the xylem (Verryckt et al, 2020). The photosynthetic capacity under saturating light (Amax) was measured at 2000 µmol m -2 s -1 .…”
Section: Functional Traitsmentioning
confidence: 99%
“…Branches were excised from the trees before dawn, immediately put in buckets filled with water and re-cut under water at least 20 cm up from the original cut, toward the tip of the branch to avoid cavitation as described previously [ 38 , 43 ]. Importantly, measurements made on cut branches show no statistically significant differences from in situ measurements on intact branches when precautions are taken to wait for acclimation and to avoid cavitation [ 44 46 ]. Gas exchange measurements and reflectance spectra were measured in a nearby shaded area.…”
Section: Methodsmentioning
confidence: 99%